SELF CONCEPT, SELF ESTEEM AND SCHOOL SYSTEM: THE STUDY OF COMPARATION BETWEEN FULLDAY SCHOOL AND HALFDAY SCHOOL IN PURWOREJO - Iftayani, Itsna; Nurhidayati, Nurhidayati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Abstract: Self concept and self esteem are two psychological aspects that need to be attention in learning at school because a high of self concept and self esteem can influence students success in their learning. The objective of this research is to know about the differences about  self concept and self esteem among elementary students with full day school and half day school system. The method used in this observation is comparison by comparing self concept and self esteem of elementary students with full day and half day system. The population of this research is 3 fullday Islamic elementary schools and 6 halfday Islamic elementary schools. The sample of this research is SD Islam Al-Madina as fullday school and SD Muhammadiyah Purworejo as halfday school. The data is gotten by the scale, observation, interviews and documentation. The result shows that there are no significant differences between self concept (t=0,096 with df :47)  and self esteem (t=0,396 with df :47) among student who study in full day school and half day (regular) school system so it means that school system doesn’t influence the quality of self concept and self esteem.Keywords: self concept, self esteem, full day school, half day school.